Pengaruh Lingkungan Kerja Non Fisik dan Motivasi Kerja Terhadap Kepuasan Kerja Guru SMK Swasta di Kabupaten Maros - Suryandari, Suryandari; Syamsul, Syamsul; Resekiani, Resekiani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research is a quantitative research that aims to determine whether or not there is an influence of non physical Work Environment and Work Motivation on Job Satisfaction of Teachers in Maros Regency (study on Private Vocational High School Teachers in Maros Regency.) Participants in this study were 129 Private Vocational High School Teachers. The measuring instruments used in this study include three scales, namely the work environment scale, the work motivation scale and the job satisfaction scale. The data analysis method of this study includes normality, linearity, multicollinearity and Multiple Linear Regression tests using SPSS 26 which thoroughly explains the influence between the variables in the study and the series testing. simultaneously.From the results of the analysis, it was found that the t-value produced on the influence of X1 on Y of 3.131 was known to be greater than the t-table, namely 3.131> 1.98 and the significance value produced was 0.002 <0.05, so H0 was rejected and H1 was accepted. It can be concluded that there is a positive and significant influence on the work environment on the job satisfaction of private vocational school teachers in Maros Regency. From the results of the analysis, it was found that the t-value produced on the influence of X2 on Y of 4.412 was known to be greater than the t-table, namely 4.412> 1.98 and the significance value produced was 0.000 <0.05, so H0 was rejected and H2 was accepted. It can be concluded that there is a positive and significant influence on work motivation on the job satisfaction of private vocational school teachers in Maros Regency. From the analysis results obtained and the large F count produced is greater than F table which is 21.501>3.07 and the significance value produced is 0.000<0.05, then H0 is rejected and H3 is accepted. It can be concluded that X1 and X2 together have a large influence on the contribution of the influence of the work environment and work motivation to job satisfaction of 25.4%.